Constitutional law analysis of the elimination of the phrase "assignment of the chief of police" in constitutional court decision no. 114/puu-xxiii/2025 - Wahyudi Wahyudi; Ujang Hibar; Dian Samudra (Journal of Law Science, 2026)
This abstract examines the constitutional law analysis of the deletion of the phrase "assignment of the Chief of Police" in Constitutional Court Decision No. 114/PUU-XXIII/2025 and its implications for the principle of state apparatus neutrality. The decision issued by the Constitutional Court sparked debate regarding the limits of the Chief of Police's authority in the context of institutional assignments, particularly those that intersect with political and state administrative interests. This study uses a normative juridical method with a statutory and conceptual approach to examine the ratio decision in the decision and its compliance with the principles of the rule of law and constitutional democracy. The results show that the deletion of the phrase is an attempt by the Constitutional Court to emphasize the importance of limiting power and maintaining the independence of the police institution from potential political intervention. From a constitutional law perspective, this decision strengthens the principle of state apparatus neutrality as part of the principles of professionalism and impartiality in governance. However, on the other hand, there are practical implications in the form of a potential normative vacuum regarding the assignment mechanism that was previously explicitly regulated, thus requiring further regulatory adjustments. In conclusion, the Constitutional Court's ruling not only has a legal dimension but also impacts institutional governance and the ethics of state administration. Therefore, regulatory harmonization and strengthened oversight are needed to ensure that the principle of state apparatus neutrality is consistently maintained in Indonesian state administration practices